THE ROLE OF EMPLOYEE ENGAGEMENT AS A MEDIATOR ON THE INFLUENCE OF ORGANIZATIONAL CULTURE ON JOB SATISFACTION AT PT. S A. - Ghozali, Muhamad Imam; Ekhsan, Muhamad (Dynamic Management Journal, 2023)
Efforts to achieve job satisfaction and culture and work engagement are very important for both individuals and organizations, where this is an organizational form factor within the company, if it is not in line with contributing well to the company, it will have a negative impact and vice versa, this shows a lack of appreciation from superiors in the company for employees, this causes job satisfaction to decrease. However, research to realize this satisfaction is very strongly influenced by the behavior of his superiors. And it has been proven that honest superiors who dare to show influencing behavior towards current employees are able to increase employee satisfaction. The purpose of this study was to determine whether there is an influence of organizational culture on job satisfaction mediated by employee engagement. Research Object at PT. S A. This research was conducted using quantitative methods with SEM Smart PLS software as analysis. The number of samples obtained by sampling technique by random sampling using the slovin formula amounted to 74 respondents. Data collection was carried out using a Google form in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects. The results of this study indicate that organizational culture has a positive and significant effect on job satisfaction. Organizational culture has a positive and significant influence on engagement. Employee engagement is able to provide a positive and significant influence on job satisfaction. job satisfaction on employees.